Analisis Informasi Akuntansi Diferensial Menjual atau Menyewakan Pada Cv Wira Jaya di Samarinda - Yesin Oktavia (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
ABSTRACT Yesin Oktavia. Analysis of Differential Accounting Information of selling or Renting at CV. Wira Jaya. Under guidance of Mrs. Nurita Affan as advisor 1 and Mrs Dhina Mustika Sari as advisor 2.The purpose of this research is to know and analyze the differential cost of two alternatives, to sell or renting the Excavator Komatsu PC 200-7 to determine which is more favorable alternative between sell or rent Excavator Komatsu PC 200-7. The formulation of this research is to determine which alternative is more favorable for CV. Wira Jaya between selling or renting Excavator Komatsu PC 200-7.Data collection methods used in this research is research field, which consist of observation, interviews, documentation, and research literature. The instrument analysis that used in this research is differential cost analysis. Whereas to calculate the interest rate using the method of debt cost and the present value method. The analytical method is performed by comparing the income and expense differential between decision to seling or renting Excavator Komatsu PC 200-7.             Analysis differential cost of the alternative decision to rent Excavator Komatsu PC 200-7 related the future costs. Therefore it is necessary to calculate interest rate or discount factor that used to determine present value. Calculating the present value is done using the present value formula with 5,1 % interest rate for two year.Based on the analysis of the differential cost of alternative selling or renting show that there is a profit difference between the decision to sell and rent. The profit that earned CV. Wira Jaya if the choose alternative to sell the Excavator Komatsu PC 200-7 is Rp1.039.200.000,- while the net profit earned of CV. Wira jaya if choose alternative to rent is Rp 1.538.866.936,-. This thing cause profit difference is Rp 499.666.936,-The result of this research show that rent Excavator Komatsu PC 200-7 alternative result the bigger cash in flow than selling Excavator Komatsu PC 200-7 alternative, because net profit result of selling alternative more profitable than net profit result of renting alternative.Suggestion of this research to management CV. Wira Jaya is making decision to rent alternative Excavator Komatsu PC 200-7 because net profit result is bigger than sell alternative Excavator Komatsu PC 200-7.  Keyword : Differential cost, decision making